Vessel traffic scheduling optimization for restricted channel in ports. (February 2021) - Li, Junjie; Zhang, Xinyu; Yang, Bingdong; Wang, Nannan
Highlights: Study the vessel traffic scheduling optimization for restricted channel in multi-harbor basins. An optimization model is proposed to ensure the safety and efficiency of vessel navigation. A heuristic algorithm is presented to obtain the vessel sequence and optimal traffic scheduling schemes. Computational experiments are conducted to verify the rationality of the model and the effectiveness of the algorithm. Abstract: Due to the narrowness and depth constraints of restricted channels, traffic conflicts and vessel delays often occur. These have seriously affected the safety and efficiency of vessel navigation, especially in ports with multi-harbor basins sharing a restricted channel. Therefore, the aim of this paper is to rank the vessels entering and leaving the restricted channel of multi-harbor basins, and generate the optimal traffic scheduling schemes for each vessel, so as to ensure the safety and efficiency of vessel navigation. In this study, through analyzing the characteristics of a restricted channel in ports, a general structure of a restricted channel in multi-harbor basins is proposed and the four key areas of vessel traffic conflict are specified. Furthermore, considering the constraints of tide, navigation continuity and navigation rules, a multi-objective optimization model of vessel traffic scheduling for restricted channel in multi-harbor basins is proposed. To obtain the vessel sequence and appropriate traffic scheduling schemes, a heuristic algorithm combining the non-dominated sorting genetic algorithm II (NSGA-II) and Tabu Search (TS) is developed to solve the mode. Finally, the experiment of different scheduling scales is generated based on the physical layout and operational data of Huanghua coal port. The experiment result shows the rationality of the proposed model and the effectiveness of the algorithm.